Safety and Efficacy of Direct Oral Anticoagulants for Treatment of Venous Thromboembolism in Pediatric Oncology Patients. Issue 1 (19th January 2023) - Scheuermann, Amanda; Liegl, Melodee; Simpson, Pippa; Branchford, Brian; Malec, Lynn
Abstract : Background/Objectives: Children with cancer have an increased risk for developing a venous thromboembolism (VTE) during their treatment course. Direct oral anticoagulants (DOACs) represent a relatively new class of oral medications to treat VTE; however, data are limited to support use in this patient group. Given the safety and efficacy data from numerous perspective adult studies, providers now consider off-label use in select children. Methods: We performed a single-center, retrospective review of children 0 to 20 years of age from 2012 to 2020 with malignancy and confirmed VTE, with the objective to evaluate the hypothesis that the safety and the efficacy of DOACs are noninferior to enoxaparin in this population. The primary composite efficacy outcome comprises symptomatic recurrent VTE, death due to VTE, and thrombus progression. The principal safety outcome is a combination of major and clinically relevant nonmajor bleeding. Results: The safety and efficacy outcomes collected revealed that DOAC use was equivalent when compared with the enoxaparin group for treatment of VTE. One patient in the DOAC group had clinically relevant, nonmajor bleeding compared with 2 patients in the enoxaparin group. No treatment failures were observed. Conclusions: This single-center study suggests that DOACs are both safe and efficacious for the treatment of VTE in children with cancer. It also highlights the need for larger studies to address this clinical question.